Determine the Efficiency of Guidance and Counselling on Students’ Academic Excellence: Selected Public Secondary Schools in Wukari Town, Taraba State - Agaba T. Jethro; Phibee Nancy Nathaniel; Ali Garba Gani (ALSYS, 2025)
This study investigates the efficiency of guidance and counselling services in promoting academic excellence among students in selected public secondary schools in Wukari Town, Taraba State, Nigeria. The research specifically examines the influence of parental involvement and the role of school counsellors in enhancing students' academic performance. Grounded in Humanistic and Cognitive-Behavioral Theories, the study adopts a quantitative approach, employing an experimental design with both a treatment (experimental) group and a control group. Data were collected using the Students’ Response at Will (SRW) instrument. The findings indicate that while there is no statistically significant difference in academic improvement between the groups, guidance and counselling services nonetheless contribute meaningfully to students’ academic development, personal growth, and social adjustment. The results underscore the importance of integrating guidance and counselling programs within the educational system as supportive mechanisms for learners. The study concludes that students lacking access to counselling services tend to underperform academically, and that such services play a crucial role in promoting educational attainment and mental well-being. Accordingly, it is recommended that parents and school counsellors collaborate with teachers to support students holistically, and that adequate resources be allocated to strengthen guidance and counselling programs in secondary schools.